IMPLEMENTATION OF STATE MINISTER OF WOMEN'S EMPOWERMENT AND CHILD PROTECTION REGULATION OF THE REPUBLIC OF INDONESIA NUMBER 8 OF 2014 CONCERNING CHILD FRIENDLY SCHOOLS (SRA) POLICIES IN BANDAR LAMPUNG: IMPLEMENTASI PERATURAN MENTERI NEGARA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK REPUBLIK INDONESIA NOMOR 8 TAHUN 2014 TENTANG KEBIJAKAN SEKOLAH RAMAH ANAK (SRA) DI BANDAR LAMPUNG - Fiky Nurita Ningsih; Juang Muhammad Nur Juanda; Toga Matthew Michael Siregar (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2023)
Quality education supports the progress of a nation. Therefore, an education system is needed as a guideline for implementing an effective and efficient educational process. The education system implemented in Indonesia has undergone many changes. That with these changes Indonesian education is increasingly progressing. For this reason, an effort is needed in order to improve the quality of education and teaching, one of which is to choose a learning strategy or a way of conveying subject matter so that an increase in student learning achievement is obtained. Child-Friendly Schools, hereinafter abbreviated as SRA, are formal, non-formal and informal education units that are safe, clean and healthy, care and have a culture of the environment, capable of guaranteeing, fulfilling, respecting children's rights and protecting children from violence, discrimination and mistreatment. and support children's participation, especially in planning, policy, learning, supervision, and complaint mechanisms related to the fulfillment of children's rights and protection in education. The purpose of this article is to find out how the implementation of the Regulation of the Minister of Women's Empowerment and Child Protection of the Republic of Indonesia Number 8 of 2014 concerning Child Friendly School Policy (SRA) in Bandar Lampung. The research method used for this research is empirical juridical or socio legal. Based on the Regulation of the State Minister for Women's Empowerment and Child Protection of the Republic of Indonesia Number 8 of 2014 concerning Child Friendly School Policy, there are several indicators that must be met in the learning component to become a Child Friendly School (SRA), namely: SRA Policy, Curriculum implementation, Educators and staff trained education on child rights, SRA facilities and infrastructure.